Acute kidney injury is a powerful independent predictor of mortality in critically ill patients: a multicenter prospective cohort study from Kinshasa, the Democratic Republic of Congo. Issue 1 (December 2016) - Masewu, Angèle; Makulo, Jean-Robert; Lepira, François; Amisi, Eric; Sumaili, Ernest; Bukabau, Justine; Mokoli, Vieux; Longo, Augustin; Nlandu, Yannick; Engole, Yannick; Ilunga, Cedric; Mosolo, Alphonse; et al.
Abstract Background Despite the growing incidence of acute kidney injury (AKI) worldwide, there is little data on the burden and outcomes of AKI in intensive care unit (ICU) in low resource settings. The present study assessed the incidence of AKI and its impact on mortality in ICU in Kinshasa (Democratic Republic of Congo). Methods In a prospective cohort study, 476 consecutive critically ill patients (mean age 52 years, 57 % male) were screened for the presence of AKI in seven ICU from January 1st to March 30th, 2015. Serum creatinine was measured by the enzymatic method (Cobas C111 device®). AKI and its stages (no AKI, AKI 1, AKI 2 and AKI 3) were defined according to AKIN recommendations. The primary outcome was 28 days mortality. Survival (time-to death) curves were built using the Kaplan Meier methods. Predictors of mortality were assessed by Cox proportional hazards regression models.p < 0.05 defined the level of statistical significance. Results The cumulative incidence of AKI was 52.7 % with AKI stage 1, 2 and 3 in 23.7 %, 16.2 % and 12.8 % of patients, respectively. Among patients who developed AKI, 146 died (58 %) vs 62 patients (28 %) in the group without AKI. Only 6.5 % of the patients with AKI stage 3 benefited from dialysis. Median survival time was 15.0 days in patients without AKI and 3.0 days, 6.0 days and 8.0 days in patients with AKI stage 3, 2 and 1 (p < 0.001), respectively. In addition to respiratory distress-induced polypnea (HRa 1.60; 95 % CI: 1.08–2.37;p = 0.018), oxygen desaturation (HRa 1.53; 95 % CI: 1.13–2.08;p = 0.006) and multi-organic involvement (HRa 1.63; 95 % CI: 1.15–2.30), AKI emerged as an independent predictor of death (HRa 1.82; 95 % CI: 1.34–2.48;p < 0.001). Conclusion More than half of critically ill patients in the present cohort developed AKI which contributed substantially to short-term mortality, highlighting the need for its prevention, early detection and management as well as the availability of dialysis in ICU.